Analysis of Healthy Living Behavior, Age, and Income on Gluten-Free Food Consumption - Hertha Bastiawan; Sugeng Santoso; Achmad Indra Sahab; Abdul Yamin; Beta Almira (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2022)
This research was triggered by the phenomenon of an increase in people adopting a healthy lifestyle during the COVID-19 pandemic. People who adopt a healthy lifestyle are assumed to consume healthy food such as gluten-free food. Meanwhile, as people grow older and their income improves, the desire to consume gluten-free food also increases. This research aims to analyze healthy behavior, age, and income on the desire to consume gluten-free foods that Logit Model constructed. Gluten-free foods can be defined as foods that do not contain gluten substances such as wheat, and they can be classified as healthy food because people who consume this food can avoid some diseases. The study determined Logit Model and used quantitative methods and convenience sampling based on the SPSS application. From 10 to 12 October 2021, research collected 193 respondents, mainly from the Jabodetabek area. Using Wald Test, the study formed a Logit Model for this relationship. In conclusion, healthy living behavior, age, and income partially and simultaneously influence gluten-free food consumption. By observing this study, entrepreneurs in the food sector are expected to produce gluten-free food.